PEMODELAN SISTEM PENJADWALAN PRAKTIKUM LABORATORIUM MENGGUNAKAN ALJABAR MAXPLUS (STUDI KASUS DI STMIK BUMIGORA MATARAM) - Uswatun Hasanah; Neny Sulistianingsih (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2015)
Practical activities carried in the laboratory which aims to support the learning process of each semester. There were 500 participants of practicum utilize this activity at every level of education D3 and S1. Therefore, it was necessary that proper schedule of system so that the process runs smoothly in the laboratory practicum. But seeing the phenomena that occur in the feld, the schedule has been collated not corresponding with time of lecturers and students so that researchers trying to model the laboratory practicum of STMIK using Maxplus algebra. Based on the model and the simulation by results of Scilabwas scheduling in the Lab II that eigenvalues for 800 with an initial value x (0), its mean the period of transition participants of practicum and the other participants of practicum is 800 minutes. Therefore, there was only one lab are scheduled every day in Lab II because the process of practicum fnished at 12.00.